Electronic Literature Communities - Baldwin, Sandy, 1966-; Tomaszek, Patricia; Rettberg, Scott (Computing literature, 2016)
This is a diverse collection on the role and function of community in the contemporary practice of electronic literature, with ten essays by thirteen leading authors, providing wide-ranging perspectives and approaches. The collection offers historical narratives of institutions in the field, examples of how particular platforms or genres can inspire community, and stories of how ad hoc communities can form around specific creative projects. These case studies are histories of creative affiliations in electronic literature--snapshots of consensus-based communities in their process of formation--and offer a starting point for broader theoretical analyses of network-based creative community.